Competitividade da cadeia produtiva do coco: visão dos extensionistas da EMATER/RN na mesorregião leste Potiguar do Rio Grande do Norte - Silva, Dione Vicente da (2009)
The present study presents an investigation concerning the factors that, in the perception of the extension of Emater/RN they affect the competitiveness of the productive chain of the coconut in Rio Grande do Norte. For so much it is used of a theory structured starting from the several aspects that delineate the competitiveness and your respective factors, besides the aspects that compose the productive chain of the coconut in Rio Grande do Norte. The research was accomplished at the mesorregião Leste Potiguar of Rio Grande do Norte, territory of larger index of coconut production in the state. The used methodological approach was the one of descriptive exploratory research together to the conduction of a rising type Survey. The field research obtained 35 valid questionnaires, whose interviewees were the extension of Emater/RN in performance in the municipal districts that compose the mesorregião Leste Potiguar of Rio Grande do Norte. The results allow to end that in the perception of the extension, the level of competitiveness of the productive chain of the coconut in Rio Grande do Norte is still low, presenting as larger fetter the low price of the coconut and the high costs of the productive process, being recommended a larger support to the producing of coconut in relation to technical attendance, incentive actions to the quality, understanding with relationship to the benefits of the creation of partnerships, associations and cooperatives, as well as the promotion of the knowledge of the productive chain of the coconut in Rio Grande do Norte for subsequent ends of all the agents' of that chain training with relationship to the importance of the development of competitive advantages